2022
DOI: 10.1111/ppl.13626
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium and nitrate affect sexually different responses to salt stress in Populus cathayana

Abstract: Nitrogen (N) fertilization is a promising approach to improve salt tolerance. However, it is poorly known how plant sex and inorganic N alter salt stress-induced Na + uptake, distribution and tolerance. This study employed Populus cathayana Rehder females and males to examine sex-related mechanisms of salt tolerance under nitrate (NO 3 À ) and ammonium (NH 4 + ) nutrition. Males had a higher root Na + efflux, lower root-to-shoot translocation of Na + , and higher K + /Na + , which enhanced salt tolerance under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Male individuals respond faster to salt stress in the presence of nitrogen, as suggested by the results of the differential expression assessment of multiple genes [303]. But under salt stress, for example, the expression of genes related to isoprenoid biosynthesis was elevated in female individuals [304]. Looking at the effects on poplar defense mechanisms, the representation of pipecolic and N-hydroxypipecolic acids increased, and SA and jasmonoyl isoleucine decreased in xylem sap when nitrogen availability increased; a number of secondary metabolites (salicinoids, phenylpropanoids, phenolic compounds, flavonoids and benzoates), with the exception of coumarins, were more actively synthesized under nitrogen deficiency [305].…”
Section: The Sex Of the Tree As A Factor In Determining The Effective...mentioning
confidence: 98%
“…Male individuals respond faster to salt stress in the presence of nitrogen, as suggested by the results of the differential expression assessment of multiple genes [303]. But under salt stress, for example, the expression of genes related to isoprenoid biosynthesis was elevated in female individuals [304]. Looking at the effects on poplar defense mechanisms, the representation of pipecolic and N-hydroxypipecolic acids increased, and SA and jasmonoyl isoleucine decreased in xylem sap when nitrogen availability increased; a number of secondary metabolites (salicinoids, phenylpropanoids, phenolic compounds, flavonoids and benzoates), with the exception of coumarins, were more actively synthesized under nitrogen deficiency [305].…”
Section: The Sex Of the Tree As A Factor In Determining The Effective...mentioning
confidence: 98%
“…+ assimilation (Liu et al, 2022). NH 4 + can also be assimilated by glutamate dehydrogenase (GDH), which converts aoxoglutarate to glutamate.…”
Section: Gene Expression Action Referencesmentioning
confidence: 99%
“…Research focus on sustaining N dynamics in managing salt stress responses gained attention. Salt stress has an impact on nitrification and ammonification in the soil as chloride (Cl -) competes with nitrate (NO 3 -) and causes ion toxicities and ionic disparities, which can explicitly restrict N uptake, transport and assimilation processes (Campbell, 1999;Zhao et al, 2020;Liu et al, 2022;Tzortzakis et al, 2022, Figure 1). Reductions in N uptake and metabolism have been reported in many plant species (Dalio et al, 2013;Singh et al, 2016;Shahzad et al, 2017;Fuertes-Mendizabal et al, 2020, Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al (2020) showed that male P. cathayana had higher tolerance than female plants under low phosphorus nutrient stress by enhancing symbiosis with mycorrhizal fungi. Under the salt stress, the addition of ammonium and nitrate nitrogen promoted male P. cathayana efflux Na + ions through the roots, and fewer Na + ions were transferred to the shoot, which makes male plants have a higher salt tolerance than female plants (Liu et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Under the salt stress, the addition of ammonium and nitrate nitrogen promoted male P . cathayana efflux Na + ions through the roots, and fewer Na + ions were transferred to the shoot, which makes male plants have a higher salt tolerance than female plants ( Liu et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%